PREVALENCE OF SYPHILIS AND HIV INFECTION AMONG MEN WHO HAVE SEX WITH MEN TESTED IN A NON-GOVERNMENTAL ORGANIZATION IN BELGRADE - Bjekic, Milan (HEALTH CARE, 2022)
Introduction/Aim: In Belgrade, syphilis and human immunodeficiency virus (HIV) infection most often occur among men who have sex with men who are often stigmatized and discriminated and hesitate to come to health institutions for testing for these diseases. The aim of this study was to assess prevalence of syphilis and HIV infection among men who have sex with men who were tested in the "check-point" center of the association "Potent" in Belgrade. Methods: This cross-sectional study included 993 participants tested for HIV and 860 participans tested for syphilis by rapid screening tests HEXAGON SYPHILIS and HEXAGON HIV. The results of rapid HIV tests were confirmed by a positive Western-Blot test at the Infectious Diseases Clinic of the Clinical Center of Serbia, and for syphilis by positive serological tests (VDRL - Venereal Disease Research Laboratory and TPHA - Treponema Pallidum Haemagglutination Assay) at the City Institute for Skin and Venereal Diseases in Belgrade. Proportions, percentages and the χ2 test were used in the statistical analysis of the data. Results: A positive test for HIV was recorded in 11 (1.1%), and a positive test for syphilis in 34 participants (3.9%). The youngest newly diagnosed HIV positive case was 22 years old and the oldest 46 years old, while the youngest case with a positive test for syphilis was 19 years old and the oldest 68. Conclusion: Strategies for testing for syphilis and HIV among men who have sex with men should be diverse, including community testing conducted by non-government organization in cooperation with health facilities.